PENGARUH KUALITAS PRODUK DAN BRAND IMAGE TERHADAP KEPUTUSAN PEMBELIAN - Supriyadi Supriyadi; Wahyu Wiyani; Ginanjar Indra Kusuma Nugraha (University of Merdeka Malang, 2017)
This study aimed to describe (1) If the variable influence on product quality product purchasing decisions Converse brand shoes. (2) Whether variables affect the brand image of the product purchase decisions Converse brand shoes. (3) Is the variable product quality and brand image influence the purchasing decisions Converse brand shoes The population in this study was students whom to be Converse brand shoes product user in Faculty of Social and Political Science at the Merdeka University of Malang, a total of 39 respondents using non-probability sampling. Data that has met the validity and reliability, and classical assumption (t test and F test) is processed to produce a regression equation as follows: Y = 13,789 + -0,261 X1 + 0,689 X2Where the purchasing decisions variable (Y), the qulity of the product (X1), and brand image (X2). Hypothesis testing using t test showed that the variable quality of the products that have been researched proved no effect on the purchasing decisions, but the variables that proved influential brand image on consumers purchasing decisions. Hypothesis testing using the F test shows that the variable quality of the product and brand image influence on purchase decisions by 22, 7%, while the remaining 77, 3% is influenced by variables that are not used in this study. DOI : https://doi.org/10.26905/jbm.v4i1.1714